Ayurvedic Management of Vipadika (Palmoplantar Psoriasis) - Dinesh Kumar Kumawat; Anita Sharma (Journal of Ayurveda)
Introduction:Psoriasis is an immune-mediated illness, in which the skin develops persistent inflammatory abnormalities. Palmoplantar psoriasis (PPP) affects about 5% of all psoriasis patients, and it is difficult to treat this type of psoriasis.Main Clinical Finding:This was a case report of a 23-year-old female, who presented with complaints of painful cracks with intermittent bleeding over the palms of hand and soles of feet. Less scaly patches and other skin changes were found over the palms of hands surface and were also associated with intense itching and burning sensation for the past 3 years.Diagnosis:Condition was diagnosed as PPP (Ayurvedic diagnosis – Vata Kapha dominant Tridoshaja Vipadika).Interventions:The patient was treated with Avipattikara + pitantaka + Suddhagandaka yoga, Mahatikta Ghruta, Arogyavardhini vati, Khadiraristha, and local application of Jivantyadi yamaka daily for 42 days.Outcome:The patient had relief in all the symptoms after 15 days of treatment with no new eruptions. Complete remission of the disease was observed after 2 months of treatment with the improved skin condition.Conclusion:This case study demonstrates the potential and usefulness of Ayurveda in the management of PPP.